The growth of creative industries in Korean cities - Ho Yeon Kim (European Regional Science Association (ERSA), 2010)
Recently, the so-called creative industry is gaining attention as a new engine of regional economic growth. Using this new industrial classification, many countries are starting to promote the cultural creation activities with the purpose of seeking out new directions in regional development. The synergy effects can also be attained by promoting the traditional sectors to the creative industry. This concept is useful not only for mega cities like Tokyo, Seoul, Beijing and Shanghai, but also for smaller local cities such as Kitakyushu, Fukuoka, Busan, Incheon, Tianjin, and Yantai. Since capital and human resources are rather limited in these local cities, applying the said concept can exert newfound energy for urban development. Although there is an old industrial culture of manufacturing embedded in Kitakyushu City, for example, the facilities and institutes of some other cultures and sports have been promoted separately. In order to reap the full benefit, it is needed to tear down the barriers between them, and combine the existing industries, facilities, and support organizations in a more systematic way. In this paper, we will explore these aspects by using census data as a general guide and interviews with selected cultural and sports organizations as well as entrepreneurs as a case study. Specifically, we will investigate the city planning practice and growth policy regarding cultivation of creative industry, and investigate possible cooperation among the cities in Pan Yellow-Sea region based on cultural or sports activities. Regarding general study, we recount the industrial classification of existing census data according to the definition of the creative industry by the UK (see London's Creative Sector: 2004 Update and Creative Industries Economic Estimates Statistical Bulletin), adding the tourism industry. Based on this definition, we can clarify the trends of creative industry at the country level and city level of Japan, China and South Korea after 1990. It would reveal the true potential of the creative industry as a long-term facilitator of the regional economy.
Keywords: 330